Jurisprudential and Psychological Approach to Dar al-Ifta’s Fatwa on Overcoming Worship Laziness Within the Framework of Modern Behavioral Challenges - Munawar, Ahmad Rifki; Cendana, Adji Saputra; Taudiyah, Nasya Tisfa (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2024)
This research aims to analyze the fatwa issued by Dar al-Ifta concerning solutions to spiritual laziness in worship, focusing on its relevance and applicability in modern Muslim contexts. Employing a qualitative content analysis methodology, the study examines primary fatwa texts alongside classical Islamic jurisprudence and contemporary psychological theories to understand the fatwa’s multi-dimensional approach. The results reveal that Dar al-Ifta advocates a gradual and mindful practice of worship, emphasizing consistent small acts to overcome inner resistance, thereby integrating spiritual and behavioral insights. This approach not only reinforces traditional Islamic teachings but also aligns with modern habit formation principles, making the fatwa particularly relevant for Muslims navigating contemporary challenges such as digital distractions and psychological fatigue. The originality of this research lies in its interdisciplinary analysis, bridging fiqh (Islamic jurisprudence) with behavioral science to provide a comprehensive understanding of spiritual laziness and its remedies. The study’s implications extend to religious scholars, counselors, and practitioners, suggesting that fatwas can function effectively as holistic tools that address both spiritual and psychological dimensions of worship. This highlights the importance of contextualizing religious rulings within modern life to enhance their practical impact and foster sustained religious commitment.